Value Added Agriculture: Is It Right for Me? - Edward Evans (EDIS)
The purpose of this article is to explore the concept of value added agricultural businesses and to provide a set of preliminary questions which may help agricultural producers decide whether a particular value added business is suitable for them.  This document is FE638, one of a series of the Food and Resource Economics Department, UF/IFAS Extension. Original publication date May 2006.